Desarrollo de herramienta de visualización y predicción de datos - Bravo Arias, Marcelo Daniel (2018)
Abstract:In the present thesis Project is realized with the end to present graphically historical data in different environments, that are generated in the observatory of Telecommunications and society of the information. these data are generated in the same observatory; At the same time, it is sought to make a prediction of these data so that they can be shown in the different available graphics. The application has a user interface that allows you to view and / or predict a set of data that can be uploaded to the platform through the same interface. The application connects to the web server through the internet or local network through a firewall and the protection system delivered by the Framework. The server will manage the storage and consumption of data, its processing and its subsequent presentation, making a data delivery only for visualization or data for prediction and visualization of results.